USPIO-enhanced magnetic resonance imaging for nodal staging in patients with head and neck cancer - Curvo-Semedo, L (2008)
PURPOSE: To determine the accuracy of ultrasmall superparamagnetic iron oxide (USPIO)-enhanced magnetic resonance imaging (MRI) for nodal staging in patients with head and neck cancer. MATERIALS AND METHODS: Twenty patients with carcinomas of the upper aerodigestive tract were prospectively enrolled. MRI was performed before and 24-36 hours after intravenous infusion of an USPIO agent, ferumoxtran-10 (Sinerem; Guerbet, France; and Combidex; Advanced Magnetics) at a dose of 2.6 mg Fe/kg using T2-weighted spin-echo and gradient-echo sequences. Surgery was performed the same day or the day after the ferumoxtran-10-enhanced MR examination. Based on MRI, selected nodes were surgically removed and directly correlated with pathology using hematoxylin-eosin (H&E) and Perls stainings. RESULTS: A total of 63 nodes were studied; 36 were nonmetastatic, 25 metastatic, and two inflammatory. Ferumoxtran-10-enhanced MRI allowed diagnosis of 24 metastatic and 30 nonmetastatic nodes, yielding a sensitivity of 96%, a specificity of 78.9%, a positive predictive value of 75%, and a negative predictive value of 96.8%, compared to 64%, 78.9%, 66.6%, and 76.9%, respectively, for nonenhanced MRI. Accuracy of ferumoxtran-10-enhanced MRI was 85.7%. The gradient-echo T2-weighted sequence was the most accurate to detect signal loss in nonmetastatic nodes. CONCLUSION: USPIO-enhanced MRI is useful for nodal staging of patients with head and neck cancers